(untitled) (Architecture Image Studies, 2025)
University study and the promotion of scientific advancement are among the most significant goals pursued by students completing their secondary education. However, students often encounter challenges when admitted to universities located in cities different from their hometowns. In such cases, the availability of suitable university dormitories becomes crucial. These dormitories must provide essential services, security, privacy, psychological comfort, and the independence necessary for students to adapt to living away from their families during the study period. This research examines the current state of dormitory buildings in several Iraqi universities, reviews international standards for student housing, and explores how services can be improved to meet students’ needs.